Challenges of managing information quality in service organizations - Al-Hakim, Latif, 1946- (Hershey, PA : Idea Group Pub., 2007)
'Incorrect and misleading information associated with an enterprise's production and service jeopardize both customer relationships and customer satisfaction, and ultimately have a negative effect on revenue. This book provides insight and support for academic professionals as well as for practitioners concerned with the management of information'--Provided by publisher
Includes bibliographical references and index
Keywords: Information technology -- Management; Information resources management -- Quality control; Database management -- Quality control; Service industries -- Information technology -- Quality control